2016
DOI: 10.1007/s00702-016-1534-5
|View full text |Cite
|
Sign up to set email alerts
|

The aetiological association between the dynamics of cortisol productivity and ADHD

Abstract: Attention-deficit/hyperactivity disorder (ADHD) has been linked to dysregulation of the hypothalamic–pituitary–adrenal (HPA) axis, indexed by salivary cortisol. The phenotypic and aetiological association of cortisol productivity with ADHD was investigated. A selected twin design using 68 male twin-pairs aged 12–15, concordant or discordant for high ADHD symptom scores, or control twin-pairs with low ADHD symptoms, based on developmentally stable parental ADHD ratings. A genetic growth curve model was applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…We did not find significant associations between cortisol levels and the surgency-extraversion, negative affect, and effortful control regulation dimensions. To further examine this relationship and confirm that arousal does not share similar underlying mechanisms with temperament in ADHD, studies using repeated measures of cortisol productivity under different active tasks [e.g., such as those used in ( 30 )] and in larger samples are warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not find significant associations between cortisol levels and the surgency-extraversion, negative affect, and effortful control regulation dimensions. To further examine this relationship and confirm that arousal does not share similar underlying mechanisms with temperament in ADHD, studies using repeated measures of cortisol productivity under different active tasks [e.g., such as those used in ( 30 )] and in larger samples are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found low awakening cortisol levels concerning ADHD diagnosis and symptoms. However, this evidence is currently inconsistent ( 26 ), with some studies showing reduced cortisol levels in ADHD ( 27 29 ) and others showing no associations with ADHD traits ( 30 ) or case-control differences ( 31 ) requiring further replication. Additionally, only children with ADHD and ODD, but not those without comorbid disruptive behavior disorders, showed lower awakening cortisol levels than controls in an earlier study ( 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…Participants were from the Neurophysiological Study of Activity and Attention in Twins (NEAAT), which has also been described elsewhere [15,5254]. The NEAAT sample consisted of a subset of adolescent twin pairs from the Twins’ Early Development Study (TEDS), which is a longitudinal population-based study of all twins born in England and Wales in 1994 to 1996 [55].…”
Section: Methodsmentioning
confidence: 99%
“…MZ and DZ cross-twin correlations on ADHD status were fixed based on heritability estimates from a meta-analysis [4], with the following parameters: h 2 = .76, c 2 = .00, e 2 = .24, consistent with rMZ = .76 ( h 2 + c 2 ) and rDZ = .38 (.5 h 2 + c 2 ). We have established, validated and successfully applied this model to investigate the link between EEG [15,52,53] and cortisol outcomes [54] with ADHD, as well as the link between brain-based measures and other low-prevalence conditions, such as schizophrenia [7679], bipolar disorder [80,81], and psychopathy [82].…”
Section: Methodsmentioning
confidence: 99%
“…Children with ADHD and SOR displayed similar cortisol patterns to typically developing children, while children with ADHD without SOR displayed lower, possibly blunted, cortisol responses . While blunted cortisol is frequently observed in children with ADHD (Ma et al, 2011;Pinto et al, 2016), it is also observed in individuals with early adversity (Bunea et al, 2017;Kuras et al, 2017), illustrating the complex relationship between sensory modulation and stress arousal patterns. Emerging models of HPA reactivity also support various trajectories of ''typical'' daily cortisol patterns (Van Ryzin et al, 2009).…”
Section: Modes Ofmentioning
confidence: 99%